ANALISIS IMPLEMENTASI KONSEP CREATING SHARED VALUE (CSV) SEBAGAI STRATEGI KEBERLANJUTAN PERUSAHAAN : STUDI KASUS DANONE-AQUA KLATEN (2004-2017) - Elfajri, Shafa Nafisah; Wahyudi, Fendy Eko (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
This research aimed to analyze the strategy of Multinational Company in bottled water sector, Danone-Aqua at Klaten Regency on maintaining its existence in the middle of rejections from surrounding community. Theory of Liberalism Interdependency and the concept of Creating Shared Value (CSV) are used to analyze the study case. The results of this research indicated a form of interdependence between company, government, and surrounding society. Government and society depend on company existence because of their economic resource limitation, while the company restructured the main interest from natural resource to social license to operate. Implementation of CSV by Danone-Aqua manifested through Aqua Lestari program in order to strengthen the form of interdependence. Strategic Philanthropic practices also used by the company to catalyze the CSV implementation.